IMPROVING STUDENTS’ VOCABULARY IN IRREGULAR AND REGULAR VERBS BY USING CROSSWORD PUZZLE - Dashela, Tarina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aim of this research is to improve students? vocabulary, especially in understanding and writing past form. This research was conducted at the ninth grade students of MTsN 1 Pontianak in academic year 2016/2017. In this research, the subject is class IX C that consists of 39 students. The researcher conducted a classroom action research. The data were collected by using direct and measurement technique. The tools of data collecting were observation checklist, field note, and test. Crossword puzzle was used as the technique in this research which was conducted in two cycles. The research findings showed that the mean score of students? vocabulary test in the first cycle was 71.57 and the second cycle was 86.41 which means it successffully passed the KKM. The improvements of this study were particularly in students? understanding past form and writing their sentences in simple past tense correctly. Keywords: Vocabulary, Irregular and Regular Verbs, Crossword Puzzle.